Squamous papilloma arising from within a branchial cleft cyst - Matthew K. Lee; Bonnie Balzer; Gene Liu (Otolaryngology Case Reports, 2020)
Purpose: To report an unusual occurrence of HPV infection manifesting as a squamous papilloma within a branchial cleft cyst. Study design/Methods: Case report and review of literature. Results: A 64-year-old male presented with a history of recurrent oropharyngeal papillomas concurrent with a cystic neck lesion. Initial FNA biopsy was suspicious for a cystic nodal metastasis of squamous cell carcinoma. Upon excision of the neck mass, histopathologic analysis revealed a squamous papilloma arising from within a branchial cleft cyst. HPV positivity was confirmed with in-situ hybridization. The patient remains disease free after 75 months of follow-up. Conclusions: HPV infections of the upper respiratory tract are potentially transmissible into the neck via a branchial anomaly. Oncologic considerations are discussed. Keywords: Human papilloma virus, Papilloma, Branchial cleft anomaly, Branchial cleft cyst